1999
DOI: 10.1191/026921699676753309
|View full text |Cite
|
Sign up to set email alerts
|

A survey of antidepressant prescribing in the terminally ill

Abstract: Depression is a symptom in a quarter of patients admitted to a palliative care unit, but little is known of how depression in terminally ill patients is treated. We reviewed 1046 consecutive patient admissions, of whom 106 (10%) were prescribed antidepressant medication while under the care of a palliative care team. Of these patients, 21 were prescribed antidepressants when under the care of the home care team, but 80 patients (76%) were started on medication during the final 2 weeks of life. There was conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
2
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 25 publications
1
50
2
8
Order By: Relevance
“…[2][3][4][5][6] Consequently, recognition, diagnosis, and treatment of depression are important. Health care professionals face the dilemma that active screening for and treatment of mood symptoms are encouraged, but may lead to overtreatment and medicalization of normal sadness.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Consequently, recognition, diagnosis, and treatment of depression are important. Health care professionals face the dilemma that active screening for and treatment of mood symptoms are encouraged, but may lead to overtreatment and medicalization of normal sadness.…”
Section: Introductionmentioning
confidence: 99%
“…In those situations where antidepressant medication is commenced, it is frequently given at inadequate doses or too late for the therapeutic effect of the drug to take place. One survey conducted in the UK palliative care units found that 76% of antidepressants were started in the past 2 weeks of life in patients with advanced cancer [32].…”
Section: Depression In Advanced Cancer and Palliative Carementioning
confidence: 99%
“…Comas et al 17 han propuesto una escala observacional que intenta paliar las dificultades en este tipo de pacientes. Sólo una pequeña parte de los enfermos con depresión recibe tratamiento específico y, generalmente, los tratamientos comienzan demasiado tarde 5,18 . Dado que una de las razones de la ausencia de tratamiento en estos pacientes son las dificultades diagnósticas, todos los autores están de acuerdo en la necesidad de utilizar fármacos si hay dudas sobre el diagnóstico 5,19 .…”
Section: Depresiónunclassified